Analysis of Advantages of Chicken Penyet Seller Using Correspondent Analysis in Payakumbuh City - Lucky Mahesa Yahya; Mutiara Citra Sari; Muhammad Alung; Sarah Faikhotul Fadilla (Jurnal Ekonomi dan Bisnis Digital, 2023)
MSMEs are the largest contributor to GDP in Indonesia to absorb labor. Therefore it is necessary to do research on UMKM products, especially geprek chicken which is of interest to the public to increase appetite. The purpose of this study was to determine the position of geprek chicken products from various chickens in the city of Payakumbuh when compared to its competitor's ayam penyet. This study uses the Correspondence Analysis method through SPSS software. The results of the study show that SMEs with ayam geprek Mahkota Ayam and Ayam Bikamari: Both of these ayam outlets have focused on increasing their product catalog by providing better variety, Mahkota Ayam can focus on good customer service. Ayam Teteh: Ayam Teteh has a focus on good customer service and has an extensive store.